2017
DOI: 10.4314/ahs.v17i2.10
|View full text |Cite
|
Sign up to set email alerts
|

Osteopontin as a marker for response to pegylated interferon Alpha-2b treatment in Chronic HCV Saudi patients

Abstract: Abstract:Background: Many recent studies support the idea that osteopontin (OPN) can be used to predict the success of pegylated interferon (PEG IFN) alpha-2b/ribavirin therapy in chronic HCV patients. Objective: Our aim was to investigate the role of plasma OPN and its gene polymorphism at nt -443 in response to PEG IFN in Saudi patients with chronic HCV. Methods: Blood was collected from 87 patients with chronic hepatitis C before treatment, then patients received PEG IFN α2b plus ribavirin combination thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…In addition, they also observed that the OPN level was associated with the IFN‐α level. Moreover, Hussein et al disclosed that in chronic hepatitis C patients, serum OPN levels at the baseline could be a reliable indicator for the IFN‐α therapeutic response, which further supports the notion that OPN can participate in modulating IFN‐α's function. In the present study, we quantified serum IFN‐α to determine the correlation between serum OPN and IFN‐α in GD and HT patients.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In addition, they also observed that the OPN level was associated with the IFN‐α level. Moreover, Hussein et al disclosed that in chronic hepatitis C patients, serum OPN levels at the baseline could be a reliable indicator for the IFN‐α therapeutic response, which further supports the notion that OPN can participate in modulating IFN‐α's function. In the present study, we quantified serum IFN‐α to determine the correlation between serum OPN and IFN‐α in GD and HT patients.…”
Section: Discussionsupporting
confidence: 88%
“…On the other hand, evidence has shown that OPN is linked to INF‐ α synthesis and function . Shinohara et al showed that OPN can stimulate IFN‐α production in mouse plasmatoid dendritic cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 A similar article by Alabi and colleagues 8 on molecular screening of antibiotic-resistant determinants among multidrug-resistant clinical isolates of Proteus mirabilis from Southwest Nigeria also makes interesting reading. We conclude this infectious diseases section with two interesting papers: osteopontin as a marker for response to pegylated interferon Alpha-2b treatment in chronic HCV Saudi patients 9 , and a VAR2CSA: CSP conjugate malaria vaccine capable of inducing dual specificity antibody responses 10 .…”
mentioning
confidence: 99%